The effect of direct hemoperfusion with polymyxin B immobilized cartridge on meropenem in critically ill patients requiring renal support - Wanchana Singhan (2019)
© 2019 Elsevier Inc. Purpose: To evaluate the effect of direct hemoperfusion with polymyxin B immobilized cartridge (DHP-PMX) on meropenem pharmacokinetics in critically ill patients with sepsis requiring continuous venovenous hemofiltration (CVVH). Material and methods: After intravenous infusion of 1 g meropenem over 3 h repeated every 8 h for at least 3 doses, 2 serial blood and ultrafiltration fluid samples were collected: one over a dose interval of meropenem with DHP-PMX therapy; and the other on the following day over a dose interval of meropenem with no DHP-PMX therapy. Meropenem concentrations were measured by high performance liquid chromatography. Pharmacokinetic parameters of meropenem and extraction ratio of DHP-PMX were calculated. Results: Mean AUC 0–8 of meropenem on DHP-PMX day was comparable to that of the DHP-PMX free day (285.2 ± 138.2 vs 297.8 ± 130.2 mg ∗ h/L; paired t-test, p =.618). No statistical significance of peak and trough concentrations, volume of distribution, sieving coefficient, or half-life were found. Extraction ratio of DHP-PMX on meropenem was 0 [0–0.03] and clearance by DHP-PMX was 0.04 [0–0.2] L/h which was not considered clinically significant. Conclusions: No significant effect of DHP-PMX on meropenem pharmacokinetics was observed among severe sepsis/septic shock patients during CVVH treatment. Trial registration: Clinical Trial Registry detail: NCT registry: 02413541 (First registered March 3, 2015, last update October 16, 2017).